Early and progressive microstructural brain changes in mice overexpressing human α-Synuclein detected by diffusion kurtosis imaging - Khairnar, Amit; Ruda-Kucerova, Jana; Szabó, Nikoletta; Drazanova, Eva; Arab, Anas; Hutter-Paier, Birgit; Neddens, Joerg; Latta, Peter; Starcuk, Zenon; Rektorova, Irena (Brain, behavior, and immunity, 2017)
Diffusion kurtosis imaging (DKI) is sensitive in detecting α-Synuclein (α-Syn) accumulation-associated microstructural changes at late stages of the pathology in α-Syn overexpressing TNWT-61 mice. The aim of this study was to perform DKI in young TNWT-61 mice when α-Syn starts to accumulate and to compare the imaging results with an analysis of motor and memory impairment and α-Syn levels. Three-month-old (3mo) and six-month-old (6mo) mice underwent DKI scanning using the Bruker Avance 9.4T magnetic resonance imaging system. Region of interest (ROI) analyses were performed in the gray matter; tract-based spatial statistics (TBSS) analyses were performed in the white matter. In the same mice, α-Syn expression was evaluated using quantitative immunofluorescence. Mean kurtosis (MK) was the best differentiator between TNWT-61 mice and wildtype (WT) mice. We found increases in MK in 3mo TNWT-61 mice in the striatum and thalamus but not in the substantia nigra (SN), hippocampus, or sensorimotor cortex, even though the immunoreactivity of human α-Syn was similar or even higher in the latter regions. Increases in MK in the SN were detected in 6mo mice. These findings indicate that α-Syn accumulation-associated changes may start in areas with a high density of dopaminergic nerve terminals. We also found TBSS changes in white matter only at 6mo, suggesting α-Syn accumulation-associated changes start in the gray matter and later progress to the white matter. MK is able to detect microstructural changes induced by α-Syn overexpression in TNWT-61 mice and could be a useful clinical tool for detecting early-stage Parkinson's disease in human patients.
Keywords: modely nemocí na zvířatech; difuzní magnetická rezonance; Brain; MRI; Parkinson’s disease; TNWT-61; Motor Skills; Transgenic mice; alpha-Synuclein; Animals; Striatum; Substantia nigra; Diffusion Magnetic Resonance Imaging; zvířata; pohybová aktivita; Memory; paměť; Disease Models, Animal; Motor Activity; mozek; myši; alfa-synuklein; Thalamus; motorické dovednosti; Mice; Parkinson Disease; Parkinsonova nemoc; Diffusion kurtosis imaging; Animal model